Reciprocal Determinism in Sita under the Crescent Moon by Annie Ali Khan: A Socio Cognitive Analysis - Rabia Hussain; Durr-e-Nayab; Syed Musharaf Hussain Shah (Journal of Management Practices, Humanities and Social Sciences, 2024)
This study explores the concept of reciprocal determinism in Sita Under the Crescent Moon by Annie Ali Khan through a socio-cognitive lens, utilizing Albert Bandura’s theory. The research examines how cognitive learning and environmental influences shape the characters’ perceptions and social behaviors, particularly within the religious and cultural contexts of Sindh and Baluchistan. By employing Belsey’s textual analysis methodology, the study highlights how societal norms, rituals, and folklore are transmitted across generations and integrated into individuals' belief systems. The findings reveal that spirituality, faith, and socio-economic conditions significantly influence human cognition and behavior, with pilgrims seeking solace in shrines and temples. The novel illustrates the interplay between personal agency, cultural traditions, and environmental factors, demonstrating how social cognition informs religious practices and daily life. This research contributes to understanding the socio-cognitive dimensions of faith-based traditions, offering insights into the psychological and cultural frameworks that shape individual and collective identities.